Deterministic Modification of CVD Grown Monolayer MoS2 with Optical Pulses. Issue 10 (18th March 2021) - Turunen, Mikko T.; Hulkko, Eero; Mentel, Kamila K.; Bai, Xueyin; Akkanen, Suvi‐Tuuli; Amini, Mohammad; Li, Shisheng; Lipsanen, Harri; Pettersson, Mika; Sun, Zhipei
Abstract: Transition metal dichalcogenide monolayers have demonstrated a number of exquisite optical and electrical properties. Here, the authors report the optical modification of topographical and optical properties of monolayer MoS2 with femtosecond pulses under an inert atmosphere. A formation of three‐dimensional structures on monolayer MoS2 with tunable height up to ≈20 nm is demonstrated. In contrast to unmodified monolayer MoS2, these optically modified structures show significantly different optical properties, such as lower photoluminescence intensity and longer fluorescence lifetime. The results suggest a novel way to modify transition metal dichalcogenide materials for mechanic, electronic and photonic applications. Abstract : Monolayer transition metal dichalcogenides (TMDs) have shown exquisite physical properties. Tuning of those properties would be highly beneficial for different applications. Here, the authors demonstrate a deterministic optical modification method to tune the topography and optical properties of monolayer MoS2 . The findings improve the applicability of monolayer TMDs and shed light on modifying their physical properties.